Automotive vehicle assembly processes and operations management - Tang, He (SAE International, 2017)
Proven technologies and processes are explored in this examination of modern automotive manufacturing. Fundamentals and applications, as well as new advances are discussed as the author bridges the gap between academic research and industrial practice. Each chapter includes review questions and research topics.
Keywords: Automobile industry and trade.; Automobiles -- Design and construction.; elektronické knihy; electronic books